2019
DOI: 10.1149/2.0631916jes
|View full text |Cite
|
Sign up to set email alerts
|

An On-Line Transient Study on Gassing Mechanism of Lithium Titanate Batteries

Abstract: Gassing at elevated temperature is the main reason for the performance degradation of lithium titanate (Li 4 Ti 5 O 12 , LTO) batteries. In this study, an in-situ device was developed and used to study on-line the transient gassing of custom-made 4.5Ah LTO/NCM pouch batteries at 1C cycling at 55°C. The gas volume and internal pressure of the batteries were recorded on-line for 1000 h, and the composition of the gas components at different times was also analyzed by on-line gas chromatography. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In all electrode materials, the increased particle surface area inherent to nanomaterials must be balanced against other performance factors such as electrode–electrolyte reactivity and cycle life as well as external factors such as cost and scalability (section 4.1). Gas generation from Li 4 Ti 5 O 12 with standard electrolytes and residual moisture is well-known , and has now also been found in TiNb 2 O 7 -based batteries. Buannic et al found that TiNb 2 O 7 gassing under reasonable but relatively harsh conditions ((i) cycling against a high voltage LiNi 0.5 Mn 1.5 O 4 cathode or (ii) storage at 45 °C against a LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathode) was equivalent to, or worse than, Li 4 Ti 5 O 12 and was a function of TiNb 2 O 7 surface area with 32 m 2 g –1 particles evolving more gas than 6 m 2 g –1 particles annealed at a higher temperature .…”
Section: Modern Insights: 2010–2020mentioning
confidence: 99%
“…In all electrode materials, the increased particle surface area inherent to nanomaterials must be balanced against other performance factors such as electrode–electrolyte reactivity and cycle life as well as external factors such as cost and scalability (section 4.1). Gas generation from Li 4 Ti 5 O 12 with standard electrolytes and residual moisture is well-known , and has now also been found in TiNb 2 O 7 -based batteries. Buannic et al found that TiNb 2 O 7 gassing under reasonable but relatively harsh conditions ((i) cycling against a high voltage LiNi 0.5 Mn 1.5 O 4 cathode or (ii) storage at 45 °C against a LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathode) was equivalent to, or worse than, Li 4 Ti 5 O 12 and was a function of TiNb 2 O 7 surface area with 32 m 2 g –1 particles evolving more gas than 6 m 2 g –1 particles annealed at a higher temperature .…”
Section: Modern Insights: 2010–2020mentioning
confidence: 99%
“…However, gassing is one of the serious issues in batteries at elevated temperatures. Over the years, there have been many publications on the gassing behavior of LTO based LIBs, which shows the keen importance of LTO electrodes on EV application [8–13] . LTO based LIBs gassing is much more severe, which limits the usage of LTO, despite its advantage for EV applications.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, there have been many publications on the gassing behavior of LTO based LIBs, which shows the keen importance of LTO electrodes on EV application. [8][9][10][11][12][13] LTO based LIBs gassing is much more severe, which limits the usage of LTO, despite its advantage for EV applications. In graphite-based LIBs, electrolyte decomposes during the initial cycle and forms a stable solid electrolyte interphase (SEI) layer.…”
Section: Introductionmentioning
confidence: 99%